2016
DOI: 10.1002/hrm.21799
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Organizational Politics in Performance Appraisal: The Role of Coaching Leaders for Age-Diverse Employees

Abstract: In this study, we examined whether a supervisor's coaching leadership style predicts the perception of organizational politics in performance appraisal (OPPA) reported by the collaborators. Additionally, we drew on social cognition and motivational lifespan development theories to hypothesize age-related differences in perceived OPPA and its link with the coaching leadership style. Using hierarchical linear modeling (HLM) on a sample of 576 employees and 112 leaders, we found that coaching leaders are perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…Goleman et al (2012) suggested that coaching is one of the leadership styles that achieves the best results, and that its main purpose is to develop employees' personal resources. Coaching leaders are oriented toward helping employees strengthen their talents by paying attention to their needs and building an effective alliance (Dello Russo et al, 2017). From a psychosocial perspective, coaching provided by leaders is suggested as an important job (social) resource that facilitate a motivational process that enhances the development of personal resources, leading to work engagement and better performance (Schaufeli and Bakker, 2004).…”
Section: Theory and Hypotheses Defining Coaching-based Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Goleman et al (2012) suggested that coaching is one of the leadership styles that achieves the best results, and that its main purpose is to develop employees' personal resources. Coaching leaders are oriented toward helping employees strengthen their talents by paying attention to their needs and building an effective alliance (Dello Russo et al, 2017). From a psychosocial perspective, coaching provided by leaders is suggested as an important job (social) resource that facilitate a motivational process that enhances the development of personal resources, leading to work engagement and better performance (Schaufeli and Bakker, 2004).…”
Section: Theory and Hypotheses Defining Coaching-based Leadershipmentioning
confidence: 99%
“…In line with this proposition, Goleman et al (2012) argued that the main purpose of coaching leaders is to develop employee's personal resources. Leaders do so in daily interactions by paying attention to their employees needs, developing a trust environment, building an effective alliance, and providing personalized learning (Ellinger et al, 2011;Dello Russo et al, 2017). In other words, leaders can foster PsyCap through the use of specific coaching skills.…”
Section: Coaching-based Leadership and Psycapmentioning
confidence: 99%
“…Goleman et al (2012) suggested that coaching is one of the leadership styles that achieves the best results, and that its main purpose is to develop employees' personal resources. Coaching leaders are oriented toward helping employees strengthen their talents by paying attention to their needs and building an effective alliance (Dello Russo et al, 2017). From a psychosocial perspective, coaching provided by leaders is suggested as an important job (social) resource that facilitate a motivational process that enhances the development of personal resources, leading to work engagement and better performance (Schaufeli and Bakker, 2004).…”
Section: Theory and Hypotheses Defining Coaching-based Leadershipmentioning
confidence: 99%
“…In line with this proposition, Goleman et al (2012) argued that the main purpose of coaching leaders is to develop employee's personal resources. Leaders do so in daily interactions by paying attention to their employees needs, developing a trust environment, building an effective alliance, and providing personalized learning (Ellinger et al, 2011;Dello Russo et al, 2017). In other words, leaders can foster PsyCap through the use of specific coaching skills.…”
Section: Coaching-based Leadership and Psycapmentioning
confidence: 99%
“…Inaccuracies may be either intentional or unintentional in nature (Kane et al, 1995). Regarding intentional inaccuracies, some raters may avoid accurate ratings due to organizational politics (i.e., to achieve the desired results for a particular individual or group) or to enhance self-image (Dello Russo, Miraglia, & Borgogni, 2017;Spence & Keeping, 2011). Others may rate leniently due to little trust in the organization's ability to fairly use the performance data (Bernardin, Orban, & Carlyle, 1981) or to avoid negative repercussions with subordinates (Longenecker, Sims, & Gioia, 1987;Spence & Keeping, 2011).…”
Section: Introductionmentioning
confidence: 99%